Modelling herbicides movement in railway embankments in Germany - Lúcia Pedrosa; Sabrina Michael; Martin Sonntag; Markus Zingelmann; Traugott Scheytt (Journal of Contaminant Hydrology, 2026)

Corrigendum to “Physics audited and uncertainty aware surrogate modeling for reactive nitrate transport in groundwater” [Sci. Total Environ. 1044 (2026) 181942] - Alireza Arab; Traugott Scheytt; Thomas Nagel; Reza Taherdangkoo (Science of The Total Environment, 2026)

Physics audited and uncertainty aware surrogate modeling for reactive nitrate transport in groundwater - Alireza Arab; Traugott Scheytt; Thomas Nagel; Reza Taherdangkoo (Science of The Total Environment, 2026)

Numerical study of water content distribution and controlling factors in and beneath a railway embankment - Lúcia Pedrosa; Christian Engelmann; Martin Binder; Sabrina Michael; Markus Zingelmann; Traugott Scheytt (Grundwasser, 2026)
As urbanization and transport demands rise, railway systems face higher risks from operational disruptions due to system failures and climate-related impacts, especially in urban areas. Understanding water flow and distribution beneath railway embankments is crucial not only for assessing potential contaminant transport in soil and groundwater but also for identifying possible structural weaknesses. This study implements numerical simulations to investigate these dynamics, focusing on a standard railway embankment designed according to German norms. The model setup includes ballast, a low-permeability protection subgrade surface layer (PSS), a subgrade (embankment base), and a subsurface to a depth of 10 m. Numerical simulations were conducted following a univariate approach. Variation parameters included key hydraulic characteristics of the embankment and subsurface. Further parameters were groundwater recharge rate, groundwater level, existence of a less permeable horizontal layer at multiple depths, and thickness of the embankment. The most sensitive parameters shaping water percolation fronts are identified as empirical coefficients (especially the Van Genuchten shape variable α), groundwater levels and hydraulic conductivity. The results indicate that the PSS layer retains the greatest amount of water from the rail system, particularly beneath the ballast. Low α values (0.8 m –1 to 7.7 m –1 ) led to total retention of water within the embankment, with no visible percolation fronts and the lowest values observed at the PSS layer. Shallow groundwater increased initial water content up to 0.30 at the PSS layer, rapidly approaching near fully water-saturated conditions. Embankments with low hydraulic conductivities (0.048 m d −1 to 1.207 m d −1 ) show the highest water contents, reaching up to 0.46, forming a clogging area prone to retain contaminants.

Physics-informed neural network surrogate for reactive nitrate transport in groundwater - Alireza Arab; Traugott Scheytt; Thomas Nagel; Reza Taherdangkoo (Advances in Water Resources, 2026)

Metal(loid)s in mining contaminated subaquatic sediments of the Berthelsdorfer Hüttenteich, Saxony, Germany - Clemens Hartmann; Richard Stanulla; Traugott Scheytt (Journal of Soils and Sediments, 2026)
Purpose Lacustrine sedimentation is a global issue, reducing the water volume and accumulating matter in reservoirs. The study focuses on the metal(loid) composition of subaquatic sediments of the Berthelsdorfer Hüttenteich reservoir, located in an ore mining affected, siliceous and sulfidic catchment in the Erzgebirge, Germany. Materials and methods Based on high-resolution subaquatic sampling of sediment cores up to 2 m thick, the granulometric spatial distribution of Al, As, Ca, Cd, Co, Cr, Cu, Fe, Li, Mg, Mn, Ni, Pb, U, V, and Zn was determined. A modified BCR sequential extraction was performed for sand and silt/clay to characterize the chemical bonding fractions of the metal(loid)s. Results and discussion Aqua regia digestion reveals significant amounts of Al (maximum 30,400 mg kg − 1 dry mass), Fe (26,100 mg kg − 1 ), Pb (2,400 mg kg − 1 ), Zn (1,700 mg kg − 1 ), Cu (158 mg kg − 1 ), As (135 mg kg − 1 ), and Cd (18 mg kg − 1 ). The granulometric spatial distribution of the metal(loid)s and their bonding fractions are primarily affected by the catchment and the sources. There is evidence that Cd, Co, Cu, Mn, Ni, Pb, U, and Zn are locally more associated with sand than with silt/clay. The non-mass-dominating metal(loid)s are bound from 31% to nearly 100% non-residual. However, with increasing depth, the non-residual concentrations are depleted. Despite the reservoir’s sink function for metal(loid)s, their concentrations in the reservoir water are negligible, indicating a slow desorption into the reservoir. Conclusions The study shows the necessity to adjust treatment and recycling strategies of these secondary raw material deposits according to their spatial distribution characteristics.

Assessment of groundwater quality around marble slurry dumping sites at Kishangarh in Rajasthan: evaluation of possible anthropogenic impacts - Vijesh Prajapat; Traugott Scheytt; Trishikhi Raychoudhury (Journal of Earth System Science, 2026)

Surrogate-model-based calibration of effective transport parameters from push-pull tests in the Horonobe aquifer (Japan) - Elena Petrova; Philipp Selzer; Stefan Kranz; Sarah Zeilfelder; Klaus H. Hebig; Isao Machida; Atsunao Marui; Guido Blöcher; Traugott Scheytt (Geothermics, 2025)

Influence of agricultural practices and environmental conditions on pharmaceuticals in recharge waters - Dibyanshu Dibyanshu; Traugott Scheytt (Science of The Total Environment, 2025)

Current research on aquifer thermal energy storage (ATES) in Germany - Ruben Stemmle; Alireza Arab; Sebastian Bauer; Christof Beyer; Guido Blöcher; Claire Bossennec; Maximilian Dörnbrack; Florian Hahn; Philip Jaeger; Stefan Kranz; Alexandra Mauerberger; Jan Niklas Nordheim; et al. (Grundwasser, 2025)
This paper reviews the current research on aquifer thermal energy storage (ATES) and mine thermal energy storage (MTES) in Germany providing descriptions of 3 low-temperature ATES (LT-ATES), 8 high-temperature ATES (HT-ATES), and 2 MTES research sites. While the overview reveals a diverse field of investigations spanning various spatial scales, research objectives, and methodologies, the predominant focus is limited to early-stage research with low technology readiness levels (TRL). The high number of HT-ATES research sites suggests greater research interest compared to LT-ATES. The integration of ATES into district heating (DH) grids in particular is a prominent research focus, yet almost none of the projects are specifically intended for practical implementation. Future research should therefore prioritize real-world demonstration projects and identify key locations, which is crucial for showcasing the benefits of ATES. The need for a streamlined regulatory framework that addresses environmental risks and ensures installation quality and efficient permit procedures is also discussed.

Emerging contaminants: assessing the release of pharmaceuticals via managed aquifer recharge - Dibyanshu Dibyanshu; Traugott Scheytt (Environmental Science and Pollution Research, 2025)
Managed aquifer recharge (MAR) is a vital water management strategy that infiltrates surface water or wastewater effluent into aquifers through soil and sediment. However, this process can introduce pharmaceutically active compounds (PhACs) and their metabolites, posing environmental risks. This study investigates the transport behavior of four selected PhACs—caffeine, carbamazepine, diclofenac, and ibuprofen—under neutral pH conditions using column experiments in both unsaturated and saturated porous media. PhACs and a tracer solution were introduced into the system, and experimental results were simulated using the CXTFIT model to determine retardation and degradation factors. Experimental findings indicate high mobility for carbamazepine and ibuprofen across both unsaturated and saturated conditions with high recovery (> 88%) and negligible degradation (< 0.05). Ibuprofen behaved similarly identical to the tracer in unsaturated medium and with small adsorption/desorption in saturation with a retardation factor of ~ 1, while carbamazepine showed slight retardation and tailing effects showing higher persistence in the water, with high dispersion in unsaturated medium. Diclofenac significantly degrades in saturated media (45% recovery) but increases release under unsaturated conditions (91% recovery). This indicates the release of diclofenac through the vadose zone but can undergo degradation and retardation in aquifers. Caffeine exhibited high retardation and degradation, with a low recovery rate (27–30%) under both conditions, suggesting that degradation or irreversible adsorption may have occurred independently of moisture content during transport. This finding highlights the differences in mobility and degradation across unsaturated and saturated zones, posing long-term contamination risks of PhACs. This underscores the need for robust monitoring and management to prevent groundwater contamination from pharmaceuticals, pathogens, and antibiotic-resistant bacteria, especially when using wastewater effluent or stormwater for recharge. Graphical Abstract

Long-distance transport of bacteriophages MS2 and phiX174 in karst aquifers - Rebecca Serbe; Ferry Schiperski; Lara Stelmaszyk; Claudia Stange; Andreas Tiehm; Traugott Scheytt (Science of The Total Environment, 2025)

Forschungsprojekt zum Umgang mit Talsperrensedimenten am Beispiel einer Stauanlage der Revierwasserlaufanstalt Freiberg, Sachsen - Richard H. Stanulla; Judy Adamek; Traugott Scheytt; Clemens Hartmann; Ute Schiller; Annett Scholz (WASSERWIRTSCHAFT, 2024)

Modeling of heat and solute transport in a fracture-matrix mine thermal energy storage system and energy storage performance evaluation - Chaofan Chen; Martin Binder; Lukas Oppelt; Yingtao Hu; Christian Engelmann; Alireza Arab; Wenjie Xu; Traugott Scheytt; Thomas Nagel (Journal of Hydrology, 2024)

Hydrogeological characterization and utilization of the Siguatepeque aquifer, Honduras - Nelson Mejia; Traugott J. Scheytt; Mario Murillo (Hydrogeology Journal, 2024)

Best practices for characterization of High Temperature-Aquifer Thermal Energy Storage (HT-ATES) potential using well tests in Berlin (Germany) as an example - Guido Blöcher; Simona Regenspurg; Stefan Kranz; Martin Lipus; Liang Pei; Ben Norden; Thomas Reinsch; Jan Henninges; Romy Siemon; Dominika Orenczuk; Sarah Zeilfelder; Traugott Scheytt; et al. (Geothermics, 2024)

Bioenergie und Grundwasser - Nico Goldscheider; Christoph Neukum; Traugott Scheytt (Grundwasser, 2021)

50 Jahre Fachsektion Hydrogeologie - Traugott Scheytt (Grundwasser, 2019)

Combining geology, hydrogeology and groundwater flow for the assessment of groundwater in the Zahrez Basin, Algeria - Fatah Bouteldjaoui; Mohamed Bessenasse; Ahmed Kettab; Traugott Scheytt (Arabian Journal of Geosciences, 2019)

Hydrogeologie und Hydrologie der Halbinsel Darß – Zwischen Meerwasserintrusion und Landnutzung - Florian Bauer; Traugott Scheytt (Grundwasser, 2019)

A tracer test to determine a hydraulic connection between the Lauchert and Danube karst catchments (Swabian Alb, Germany) - Paul Knöll; Traugott Scheytt (Hydrogeology Journal, 2018)

Vier Jahre Editorenteam der Grundwasser – Die Mischung macht’s - Traugott Scheytt; Gudrun Massmann (Grundwasser, 2017)

Ihre Grundwasser – wohin soll’s gehen? - Traugott Scheytt; Gudrun Massmann (Grundwasser, 2017)

Hydraulic linkage of a storm water tank to a karst spring (Gallusquelle) - Morgan Tranter; Ferry Schiperski; Johannes Zirlewagen; Traugott Scheytt (Grundwasser, 2017)

Im Spannungsfeld von Wasserwirtschaft und Energie - Traugott Scheytt; Gudrun Massmann (Grundwasser, 2016)

Vergleich unterschiedlicher Methoden zur Entnahme von Feststoffproben für mikrobielle Untersuchungen - Traugott Scheytt; Jana von Freyberg (Grundwasser, 2015)

Diskussion belebt das Geschäft - Traugott Scheytt; Gudrun Massmann (Grundwasser, 2015)

Kommentar zur Veröffentlichung von Gutjahr, S., Bork, J. und Hahn, H.J.: Grundwasserfauna als Indikator für komplexe hydrogeologische Verhältnisse am westlichen Kaiserstuhl in Grundwasser 18 (3), 173–184 (2013) - Traugott Scheytt (Grundwasser, 2014)

Nichts ist beständiger als der Wandel - Neues Editorenteam bei der Zeitschrift Grundwasser - Gudrun Massmann; Traugott Scheytt (Grundwasser, 2014)

Transport of primidone, carbamazepine, and sulfamethoxazole in thermally treated sediments—laboratory column experiments - Beate Müller; Traugott Scheytt; Gesche Grützmacher (Journal of Soils and Sediments, 2013)

Interpretation und Bewertung der Rückhalte- und Abbauvorgänge im Abstrom der Deponie Monte Scherbelino, Frankfurt a.M. - Traugott Scheytt; Andreas Fach; Heiko Gerdes; Markus Kämpf; Marion Kapp; Anette Spinola (Grundwasser, 2012)

Erratum: Pharmaceuticals as indictors of sewage-influenced groundwater - Beate Müller; Traugott Scheytt; Martin Asbrand; Andrea Mross de Casas (Hydrogeology Journal, 2012)

Pharmaceuticals as indictors of sewage-influenced groundwater - Beate Müller; Traugott Scheytt; Martin Asbrand; Andrea Mross de Casas (Hydrogeology Journal, 2012)

Einsatz von Direct Push im Rahmen von Sanierungsuntersuchungen – Fallbeispiel Elsterwerda (Brandenburg) - Dirk Radny; Carsten Leven; Johannes Flachowsky; Traugott Scheytt; Peter Dietrich (Grundwasser, 2012)

Hydrochemistry of surface water and groundwater from a fractured carbonate aquifer in the Helwan area, Egypt - FATHY A ABDALLA; TRAUGOTT SCHEYTT (Journal of Earth System Science, 2012)

Passive Probennahme mit Keramikdosimetern: Möglichkeiten und Grenzen der Einsetzbarkeit - Dirk Radny; Traugott Scheytt; Hansjörg Weiß (Grundwasser, 2011)

A New Approach to Calculate EMEA’s Predicted Environmental Concentration for Human Pharmaceuticals in Groundwater at Bank Filtration Sites - Beate Müller; Traugott Scheytt; Matthias Zippel; Stephan Hannappel; Jutta Klein-Goedicke; Klaus Duscher (Water, Air, & Soil Pollution, 2011)

Investigative approaches to determine exchange processes in the hyporheic zone of a low permeability riverbank - Stefan Banzhaf; Andreas Krein; Traugott Scheytt (Hydrogeology Journal, 2011)

Untersuchung ausgewählter Oberflächen-, Grund- und Bodenwasserproben auf Perchlorat in Deutschland: Erste Ergebnisse - Traugott J. Scheytt; Jessika Freywald; Carol J. Ptacek (Grundwasser, 2011)

Erwiderung zum Kommentar von Dr. Kurt-Heiner Krieger zum Beitrag „Auswirkung einer künstlichen Hochwasserwelle auf den fließgewässernahen Grundwasserleiter“ von Banzhaf & Scheytt in Grundwasser (2009) 14(4): 265–275 - Stefan Banzhaf; Traugott Scheytt (Grundwasser, 2010)

Tracing Pharmaceuticals in the Unsaturated Zone (10 pp) - Traugott J. Scheytt; Petra Mersmann; Elzbieta Rejman-Rasinski; Anja These (Journal of Soils and Sediments, 2007)

1-Octanol/Water Partition Coefficients of 5 Pharmaceuticals from Human Medical Care: Carbamazepine, Clofibric Acid, Diclofenac, Ibuprofen, and Propyphenazone - Traugott Scheytt; Petra Mersmann; Ralph Lindstädt; Thomas Heberer (Water, Air, & Soil Pollution, 2005)

Vorkommen und Verhalten eines Arzneimittels (Clofibrinsäure) im Grundwasser - Traugott Scheytt; Susanne Grams; Holger Fell (Grundwasser, 1998)